Comparison of the Effectiveness of Passion Fruit Extract Soaking and Alkaline Peroxide on Candida albicans Adhesion as Denture Cleaning Agents - Cindy Denhara Wijaya; Susianin Tarigan; Syalaiska Alkila Sugit; Insan Munawar Batubara (Jurnal Penelitian Pendidikan IPA, 2026)
Heat-cured acrylic resin dentures are widely used to restore mastication and aesthetics in individuals with tooth loss; however, their surface characteristics may facilitate Candida albicans adhesion, increasing the risk of denture stomatitis. Therefore, effective denture cleansers are required to inhibit fungal colonization. Purple passion fruit (Passiflora edulis Sims) contains bioactive compounds with antifungal potential and may serve as a natural alternative denture cleanser. This study aimed to compare the effectiveness of 15% purple passion fruit peel and pulp extracts with alkaline peroxide in reducing Candida albicans adhesion on heat-cured acrylic resin surfaces. This laboratory experimental study employed a posttest-only control group design using pure Candida albicans isolates. Heat-cured acrylic resin specimens (10 × 10 × 2 mm) were prepared and randomly divided into four groups (n = 6): 15% peel extract, 15% pulp extract, alkaline peroxide (positive control), and distilled water (negative control). All specimens were immersed for 15 minutes in the respective solutions. Fungal adhesion was quantified using a colony counter, and the data were analyzed using the Kruskal–Wallis test followed by the Mann–Whitney post hoc test. The results showed mean colony counts of 832.17 ± 34.79 CFU/mL for the peel extract group, 172.83 ± 35.02 CFU/mL for the pulp extract group, 1,006.50 ± 80.36 CFU/mL for the alkaline peroxide group, and 3,307.33 ± 114.38 CFU/mL for the distilled water group. Statistical analysis revealed significant differences among all groups (p < 0.05). The 15% purple passion fruit pulp extract demonstrated the greatest antifungal effectiveness, which may be attributed to its higher concentration of antifungal phytochemicals compared to the peel extract and the conventional cleanser. In conclusion, both 15% purple passion fruit peel and pulp extracts are more effective than alkaline peroxide in inhibiting Candida albicans adhesion on denture surfaces, with the pulp extract showing the strongest antifungal activity.